The Meaning of symbolic in Bodho Apem Tradition as Social Solidarity Media on Jepara Indonesia - Asyadily, Muhamad Hasan; Jannah, Siti Nor (Advances in Humanities and Contemporary Studies, 2023)
The bodho apem tradition is a cultural tradition that is still practiced in Jepara Indonesia, this tradition is held every Friday Pon in the month of Shawwal. The people of Jepara still preserve and maintain the bodho apem as a legacy from their ancestors which has a symbolic meaning as well as a manifestation of their supernatural expression, both with God, their ancestors, and with their lives as members of the community. Tradition bodho apem which has a symbolic meaning contained in the offerings and procedures of the bodho apem which contains good advice, values, but only a few of the people of Jepara are aware of it. This article uses a qualitative descriptive approach and the types of research used in this research are field research and the theory of symbolic interactionism from George Herbert Mead and the theory of social solidarity from Emile Durkheim. From the results of this study, it was found that the implementation of the bodho apem is a legacy of the ancestors to commemorate the story of the prophet Noah AS who was ordered by Allah to build a ship. Before carrying out the bodho apem tradition, perform a slametan by bringing apem, juroh, and offerings to be prayed for, and distributed back to the community. This activity from the bodho apem is a form of community effort in increasing the relationship between residents, as an expression of gratitude to Allah and also an apology. Tradition bodho apem has a symbolic meaning as a medium of social solidarity, namely: prioritizing common interests, cooperation, friendship or cohesiveness, togetherness in the slametan, strengthening the relationship between neighbors by bringing apem cake as a symbol of apology as well as hope in order to maintain harmony, cohesiveness, patience, unity, and a unanimous determination like the apem they share.